Observations on the fauna directly connected with sedges of the genus Cyperus in Costa Rica, Central America I. Sibariops confusus (Boh) (Col., Curculionidae) on Cyperus ferax L. Rich - Parnell, J. R. (1968)
Sibariops confusus adults oviposit in the stems of the sedge Cyperus ferax in Costa Rica. The resulting larvae feed on the stem tissues of this plant and bore downwards as they increase in size. The presence of large numbers of larva e within a stem often causes the death of the upper regions of the plant.The larvae pupate at the base of the stem and adult weevils emerge from the decaying remains of the plant. The morphology of the eggs and of the last instar larvae is included, together with measurements distinguishing the last instar larvae from the penultimate instar.